Fostering Literacy Culture at SD Negeri Tanah Merah: Success of Educational Seminar and Its Positive Impact on the Community - Afrida Erayani; Ester Julinda Simarmata; Rosdiana Samosir (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This community service aims to increase awareness and implementation of literacy culture at Tanah Merah State Elementary School, Aceh Tamiang. By holding a one-day seminar on January 10 2024, this program brings together participants from various parties, including teachers, students and parents, in a united effort to create awareness of the importance of literacy as the main foundation of education. Keynote lectures and interactive discussions in seminars dive deeper into the concept of literacy, which includes not only reading and writing skills but also critical thinking skills, interpretation, and thorough knowledge of various types of texts. This seminar also provides a platform to produce actual action plans, which reflect participants' commitment to integrating literacy culture in everyday life. Evaluation and reflection findings revealed that this activity was successful in providing positive changes in attitudes and understanding, with awards given at the end of the event as appreciation for the participants' commitment. By expressing the conclusions of this service, this abstract shows the success of the initial steps in improving literacy culture at Tanah Merah State Elementary School. This aims to ensure that the enthusiasm and understanding that emerges from this activity can become a catalyst for sustainable change at the school level and in the local community.